Engaging students through writing: A collaborative journey - Drennan, L.M. (South African Journal of Higher Education, 2017)
Access to and success in South African higher education present several challenges, particularly on an academic literacy front. Yet, higher education institutions are expected to ensure that students make a success of their studies. A plausible response to this challenge is to change the approach to academic literacy and writing within the disciplines. The paper discusses how the current practices at the writing centre of the University of the Free State aim to address students’ subject-specific writing needs in collaboration with disciplinary academics. The data from two collaborative initiatives demonstrates positive perceptions of the writing interventions, as well as a possible impact on students’ writing performance. There is, however, a need to investigate, by means of further detailed case studies, the impact of a more collaborative writing-intensive approach to writing on student performance within the disciplines. The impact of a more collaborative writing-intensive approach to writing on student performance within the disciplines needs to be investigated by means of further detailed case studies.